2021
DOI: 10.1136/jitc-2020-001910
|View full text |Cite
|
Sign up to set email alerts
|

Homocitrullination of lysine residues mediated by myeloid-derived suppressor cells in the tumor environment is a target for cancer immunotherapy

Abstract: BackgroundHomocitrullination is the post-translational modification of lysine that is recognized by T cells.MethodsThis study identified homocitrullinated peptides from aldolase, enolase, cytokeratin and binding immunoglobulin protein and used human leukocyte antigen (HLA) transgenic mice to assess immunogenicity by enzyme-linked immunosorbent spot assay. Vaccine efficacy was assessed in tumor therapy studies using HLA-matched B16 melanoma expressing constitutive or interferon γ (IFNγ)-inducible major histocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 52 publications
(54 reference statements)
1
20
0
Order By: Relevance
“…Mouse MHC II from Balb/c and C57Bl/6 strains can mediate homocitrulline specific responses (19,27), while for human HLA alleles, responses to the synthetic JED homocitrullinated peptide can be induced in transgenic HLA-DR4 mice (27). Furthermore, we have previously shown responses to several homocitrullinated peptides in transgenic HLA-HHDII/DP4 mice (22).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Mouse MHC II from Balb/c and C57Bl/6 strains can mediate homocitrulline specific responses (19,27), while for human HLA alleles, responses to the synthetic JED homocitrullinated peptide can be induced in transgenic HLA-DR4 mice (27). Furthermore, we have previously shown responses to several homocitrullinated peptides in transgenic HLA-HHDII/DP4 mice (22).…”
Section: Introductionmentioning
confidence: 80%
“…We have previously shown that homocitrullinated peptides can stimulate responses restricted through the HLA-DP4 allele (22). In this study we first aimed to determine whether peptide immunization can induce homocitrulline-specific responses via HLA types other than the HLA-DP4 allele.…”
Section: Homocitrulline-peptide Responses Can Be Induced Through Mult...mentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment analysis results showed that the DEGs between high and low PRS-score subgroups were mainly enriched in interferon-gamma mediated signaling pathways, antigen processing, and peptide antigens presented via MHC class II, peptide binding. The MHC-II is the critical component of adaptive anti-tumor immunity, and its upregulation is closely associated with increased levels of interferon-gamma in tumors (Dubrot et al, 2014;Cook et al, 2021). During inflammation, epithelial cells could act as accessory antigen-presenting cells along with the expression of MHC-II (Ghasemi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These cells can inhibit tumor progression by recognizing and killing tumor cells. Thus, immunotherapy has emerged as an effective therapeutic approach to killing tumor cells by activating immune responses ( 12 , 13 ). However, as compared to other cancers, there have been fewer investigations into immunotherapy for OS.…”
Section: Introductionmentioning
confidence: 99%